2020
DOI: 10.1016/j.omtm.2020.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Suprachoroidal and Subretinal Injections of AAV Using Transscleral Microneedles for Retinal Gene Delivery in Nonhuman Primates

Abstract: Retinal gene therapy using adeno-associated viruses (AAVs) is constrained by the mode of viral vector delivery. Intravitreal AAV injections are impeded by the internal limiting membrane barrier, while subretinal injections require invasive surgery and produce a limited region of therapeutic effect. In this study, we introduce a novel mode of ocular gene delivery in rhesus macaques using transscleral microneedles to inject AAV8 into the subretinal or suprachoroidal space, a potential space between the choroid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 61 publications
(76 reference statements)
0
99
0
Order By: Relevance
“…These results are consistent with our prior study which demonstrated higher concentrations of serum NAbs from intravitreal than suprachoroidal or subretinal AAV8 as measured using an in vitro transduction inhibition assay. 21 By contrast, only animals that received suprachoroidal AAV8 developed anti-GFP antibodies, which reached the highest levels at month 3, while the animal that received only intravitreal AAV8 did not ( Figure 3B). As Rhesus 02 received high-dose suprachoroidal AAV8 in both eyes, we further validated the humoral response to GFP by performing flow cytometry on peripheral blood mononuclear cells (PBMCs) collected from the serum of this animal, and found expansion of GFP-responsive plasma B-cells (CD19-,CD27+,CD38+, HLADRlow) after suprachoroidal AAV8 injection ( Figure 3C, Supplementary Figure 1) which likely accounts for the greater production of systemic anti-GFP antibodies.…”
Section: Humoral Immune Responses After Suprachoroidal Aav8mentioning
confidence: 94%
See 3 more Smart Citations
“…These results are consistent with our prior study which demonstrated higher concentrations of serum NAbs from intravitreal than suprachoroidal or subretinal AAV8 as measured using an in vitro transduction inhibition assay. 21 By contrast, only animals that received suprachoroidal AAV8 developed anti-GFP antibodies, which reached the highest levels at month 3, while the animal that received only intravitreal AAV8 did not ( Figure 3B). As Rhesus 02 received high-dose suprachoroidal AAV8 in both eyes, we further validated the humoral response to GFP by performing flow cytometry on peripheral blood mononuclear cells (PBMCs) collected from the serum of this animal, and found expansion of GFP-responsive plasma B-cells (CD19-,CD27+,CD38+, HLADRlow) after suprachoroidal AAV8 injection ( Figure 3C, Supplementary Figure 1) which likely accounts for the greater production of systemic anti-GFP antibodies.…”
Section: Humoral Immune Responses After Suprachoroidal Aav8mentioning
confidence: 94%
“…Experiments to evaluate the transduction efficacy, pattern, durability, and cell-type specificity of suprachoroidal AAV8 injections in rhesus macaques using transscleral microneedles have been previously described. 21 Briefly, we identified 5 animals between age 4-10 years with no pre-existing NAbs against AAV8, and injected both eyes with NHP-grade AAV8 that expresses enhanced GFP under a cytomegalovirus (CMV) promoter at 7 x 10 11 vg/eye (low dose) or 7 x 10 12 vg/eye (high dose), using either a 700-m long 30-gauge microneedle (Clearside Biomedical, Alpharetta, GA, USA) for suprachoroidal or transscleral subretinal injection, or a 0.5-inch-long 30-gauge conventional needle for intravitreal injection (Supplementary Table 1). Of these, two animals received suprachoroidal AAV8 in both eyes (Rhesus with x 10 11 vg/eye and Rhesus 02 with 7 x 10 vg/eye), two animals (Rhesus and 04) received suprachoroidal injection of AAV8 in one eye (7 x 10 12 vg/eye) and subretinal delivery of AAV8 in the contralateral eye (7 x 10 12 vg/eye), and the last animal (Rhesus 05) received intravitreal injection of AAV8 in both eyes (7 x 10 12 vg/eye).…”
Section: Study Design and Clinical Coursementioning
confidence: 99%
See 2 more Smart Citations
“…More recently, microneedle-based suprachoroidal gene delivery was investigated in NHPs. 31 In this study, Yiu et al compared GFP expression among suprachoroidal, subretinal, and intravitreal gene delivery of AAV8 containing an expression cassette encoded for enhanced GFP under a ubiquitous CMV promoter, woodchuck hepatitis virus post-transcriptional regulatory element, and bovine growth hormone polyadenylation signal. Suprachoroidal injection of AAV8-eGFP resulted in widespread peripheral and circumferential transgene expression in RPE, while subretinal AAV8 produced focal transduction in the RPE, PRs, and some ganglion cells, and intravitreal AAV8 resulted in GFP expression in cells, possibly astrocytes, or Müller glia, in peripapillary region.…”
Section: Suprachoroidal Viral Vector-based Retinal Gene Deliverymentioning
confidence: 99%